Impact of Fibronectin Knockout on Proliferation and Differentiation of Human Infrapatellar Fat Pad-Derived Stem Cells - Wang, Yiming; Fu, Yawen; Yan, Zuoqin; Zhang, Xiao-Bing; Pei, Ming (Frontiers in Bioengineering and Biotechnology, 2019)
Fibronectin plays an essential role in tissue development and regeneration. However, the effects of fibronectin knockout (FN1-KO) on stem cells’ proliferation and differentiation remain unknown. In this study, CRISPR/Cas9 generated FN1-KO in human infrapatellar fat pad-derived stem cells (IPFSCs) was evaluated for proliferation ability including cell cycle and surface markers as well as stemness gene expression, and for differentiation capacity including chondrogenic and adipogenic differentiation. High passage IPFSCs were also evaluated for proliferation and differentiation capacity after expansion on decellularized ECM (dECM) deposited by FN1-KO cells. Successful FN1-KO in IPFSCs was confirmed by Sanger sequencing and Inference of CRISPR Edits analysis (ICE) as well as immunostaining for fibronectin expression. Compared to the GFP control, FN1-KO cells showed an increase in cell growth, percentage of cells in the S and G2 phases, and CD105 and CD146 expression but a decrease in expression of stemness markers CD73, CD90, SSEA4, and mesenchymal condensation marker CDH2 gene. FN1-KO decreased both chondrogenic and adipogenic differentiation capacity. Interestingly, IPFSCs grown on dECMs deposited by FN1-KO cells exhibited a decrease in cell proliferation along with a decline in CDH2 expression. After induction, IPFSCs plated on dECMs deposited by FN1-KO cells also displayed decreased expression of both chondrogenic and adipogenic capacity. We concluded that FN1-KO increased human IPFSCs’ proliferation capacity; however, this capacity was reversed after expansion on dECM deposited by FN1-KO cells. Significance of fibronectin in chondrogenic and adipogenic differentiation was demonstrated in both FN1-KO IPFSCs and FN(-) matrix microenvironment.